Preliminary Study on Antifungal Activity of Soursop Leaf Crude Extract (Annona muricata L.) towards Fungi Isolated from Bolu Paranggi Cake - Andi Ita Juwita; Nur Faidah Munir; Arnida Mustafa (Journal of Biological Science and Education, 2022)
Soursop leaf extract (Annona muricata L.) contains a many potential active compounds, one of which is antifungal. Bolu Paranggi is a traditional cake from Mandar (West Sulawesi), made from wheat flour and brown sugar so it is at risk of being damaged and overgrown with fungus. This study aimed to extract soursop leaves using double RO (Reverse Osmosis) water solvent with variations in extraction time and the ratio of soursop leaf mass and water volume, identify groups of secondary metabolites compounds from soursop leaf water extract, isolate and identify fungi in Paranggi Bolu cake, and perform antifungal activity test of soursop leaf extract against fungi isolated from Paranggi Bolu cake. Extraction of soursop leaves using double RO water as a solvent with maceration for 24 hours and heating for 15 minutes with a variation of the ratio of soursop leaf mass and water volume of 1:1; 1:1.5; 1:2; 1:2.5; and 1:3. The analysis of the secondary metabolite compound was analyzed using the phytochemical test method and antifungal activity using the agar diffusion method on PDA (Potato Dextrose Agar) media and then measuring the inhibition zone using 6 mm diameter paper discs. The results showed that extraction with the heating method for 15 minutes produced more extract than the 24-hour maceration method at room temperature (RT), where the highest amount of extract was obtained from the ratio of soursop leaf mass and water volume of 1:3. The results of the phytochemical analysis of soursop leaf water extract, both heating and maceration methods, contained flavonoids, alkaloids, terpenoids, steroids and saponins, and antifungal activity tests against Aspergillus isolated from Bolu Paranggi showed weak antifungal activity at extract concentrations of 5,000 ppm - 50,000 ppm. with an inhibition zone diameter of 2 mm. Keywords: soursop leaf extract, antifungal, Bolu Paranggi cake